Influence of Transformational and Transactional Leadership on Individual Performance in the Malaysian Public Sectors - Che Mahir, Ariffin (2011)
The main purpose of this study is to examine the relationships between transformational and transactional leadership with individual performance that consists of management and non management employees in the public sectors. The data was collected from 102 respondents using a structured questionnaire. The data was analyzed using SPSS 12.0. Three main hypotheses were tested using Pearson product- moment correlation coefficient. Results of the study indicate positive significance relationships exist between transformational and transactional leadership with individual performance.